A contribution to the theory of financial fragility and crisis - Amit Bhaduri (Levy Economics Institute of Bard College, 2010)
The paper examines three aspects of a financial crisis of domestic origin. The first section studies the evolution of a debt-financed consumption boom supported by rising asset prices, leading to a credit crunch and fluctuations in the real economy, and, ultimately, to debt deflation. The next section extends the analysis to trace gradual evolution toward Ponzi finance and its consequences. The final section explains the link between the financial and the real sector of the economy, pointing to an inherent liquidity problem. The paper concludes with comments on the interactions between the three aspects.
Keywords: D84; E12; E21; E32; E41; E44; E51; G12; G18; G24; N22; 330; capital gains; consumer debt; debt-driven fluctuations; effective demand; financial fragility; liquidity preference; Vermögenszuwachs; Private Verschuldung; Bubbles; Gesamtwirtschaftliche Nachfrage; Finanzmarktkrise; Liquiditätspräferenz; Theorie